An exploratory study on institutional repository, social networking, and bibliographic databases of scholarly communication in Nigeria's academic landscape. Issue 1 (27th May 2018) - Okiki, Olatokunbo Christopher; Odunlade, Racheal Opeyemi
Abstract: This study seeks to explore institutional repository, social networking, and bibliographic databases of scholarly communication in Nigeria. Six institutional repositories (IR) were selected and five leading authors had their works manually crosschecked in two citation indexes and self-archived in social networking sites. The results reveal that faculty members have embraced self-archive on academic social network platforms, while their records in the IR do not reflect this. The study recommends Universities' management to implore academics to self-archive their publications into their IR, while the libraries too could search bibliographic databases and social network sites to update their respective IR platforms.